Portfolio diversification in concentrated bond and loan portfolios - Paul H. Kupiec (American Enterprise Institute (AEI), 2015)
In this working paper, Paul Kupiec develops an algorithm to approximate the loss rate distribution for fixed income portfolios with obligor concentrations.
Keywords: A; 330; capital requirements; Bank regulation